GINGER ESSENTIAL OIL SYNTHESIS BETWEEN CHINA AND KUCHING LOCAL GINGER FOR INSECT REPELLENT - WONG FONG FEI, - (Universiti Malaysia Sarawak, 2022)
Ginger essential oil is the violate oil extracted from ginger rhizome itself. The present of the essential oil on a plant usually is in small amount and the quantity extracted will be varying with the essential oil extraction method. Hydro distillation, steam distillation, solvent extraction, and cold press extraction is some of the examples for essential oil extraction. Comparing to the chemical synthetic mosquito repellent, green mosquito repellent would be favour by the public recently as it is environmentally friendly and does not harm to the human’s health. Some of the essential oil had been proven to have the repellent ability against the mosquito including the ginger essential oil. Hence, the focus of this study is on the comparison study between China and Kuching local ginger essential oil as the green mosquito repellent. The ginger essential oils are extracted by using hydro distillation method for 7 hours. The percentage oil yield for China and Kuching local ginger are 0.158 wt. % and 0.264 wt. % respectively. The extracted ginger essential oils are further done for Fourier Transform Infrared Spectroscopy (FTIR) and Gas Chromatography- Mass spectrometry (GC-MS) analysis. Based on the generated FTIR spectrum graph, both types of ginger essential oils have the same function groups including phenolic compounds, alcohol primer, alkena methyl group, aromatic compound, carbonyl compound, carboxylic acid, hydroxyl group. From the GC-MS results it revealed that the most abundant chemical constituents presented in the both China and Kuching local ginger essential were: α-Zingiberene (7.88% and 7.03%), α-Curcumene (6.04% and 6.49%), α-Citral or Genarial (3.81% and 7.86%), β-Bisabolene (3.06% and 4.62%), βSesquiphellandrene (5.83% and 5.95%), β-Sesquisabinene (0.07% and 0.51%), β-Selinenol (3.97% and 2.26%), Zingiberenol (5.16% and 1.64%), [6]-Shogaol (0.33% and 0.23%), transSesquisabinene hydrate (1.72% and 2.87%), trans-Geranylgeraniol (3.51% and 2.81%), Camphene (1.17% and 0.56%), Eucalyptol (2.68% and 1.81%), Citronellol (1.76% and 1.55%), Neral (2.82% and 6.03%), and Geraniol (1.62% and 2.29%) respectively. Kuching local ginger essential oil is chosen as the more suitable mosquito repellent due to its higher monoterpene compounds in ginger essential oil.